A prospective evaluation of hippocampal radiation dose volume effects and memory deficits following cranial irradiation. Issue 2 (November 2017) - Ma, Ting Martin; Grimm, Jimm; McIntyre, Riley; Anderson-Keightly, Heather; Kleinberg, Lawrence R.; Hales, Russell K.; Moore, Joseph; Vannorsdall, Tracy; Redmond, Kristin J.
Abstract: Background and purpose: To prospectively evaluate hippocampal radiation dose volume effects and memory decline following cranial irradiation. Material and methods: Effects of hippocampal radiation over a wide range of doses were investigated by combining data from three prospective studies. In one, adults with small cell lung cancer received hippocampal-avoidance prophylactic cranial irradiation. In the other two, adults with glioblastoma multiforme received neural progenitor cell sparing radiation or no sparing with extra dose delivered to subventricular zone. Memory was measured by the Hopkins Verbal Learning Test-Revised Delayed Recall (HVLT-R DR) at 6 months after radiation. Dose–volume histograms were generated and dose–response data were fitted to a nonlinear model. Results: Of 60 patients enrolled, 30 were analyzable based on HVLT-R DR testing completion status, baseline HVLT-R DR and intracranial metastasis/recurrence or prior hippocampal resection status. We observed a dose–response of radiation to the hippocampus with regard to decline in HVLT-R DR. D50% of the bilateral hippocampi of 22.1 Gy is associated with 20% risk of decline. Conclusions: This prospective study demonstrates an association between hippocampal dose volume effects and memory decline measured by HVLT-R DR over a wide dose range. These data support a potential benefit of hippocampal sparing and encourage continued trial enrollment.